2020
DOI: 10.3390/math8050768
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Architecture for Segmenting Maxillary Sinuses on Texture-Enhanced Occipitomental View Radiographs

Abstract: Maxillary sinuses are the most prevalent locations for paranasal infections on both children and adults. Common diagnostic material for this particular disease is through the screening of occipitomental-view skull radiography (SXR). With the growing cases on paranasal infections, expediting the diagnosis has become an important innovation aspect that could be addressed through the development of a computer-aided diagnosis system. As the preliminary stage of the development, an automatic segmentation over the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…10 Recently, there is emerging evidence suggesting that using deep learning models in the diagnosis of maxillary sinusitis on Waters’ view radiograph was associated with superior accuracy. 23–26 In our study, we found that sinus plain films had very high sensitivity in diagnosing both fungal and bacterial maxillary sinusitis (100% and 96.2%, respectively). There are two possible reasons.…”
Section: Discussionmentioning
confidence: 56%
“…10 Recently, there is emerging evidence suggesting that using deep learning models in the diagnosis of maxillary sinusitis on Waters’ view radiograph was associated with superior accuracy. 23–26 In our study, we found that sinus plain films had very high sensitivity in diagnosing both fungal and bacterial maxillary sinusitis (100% and 96.2%, respectively). There are two possible reasons.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies used machine learning tools due to the development and advancement in machine learning techniques for classification and detection tasks [ 24 ]. Various machine learning techniques were proposed to analyze and detect human emotion from EEG signals.…”
Section: Related Orkmentioning
confidence: 99%
“…With the advancement of computer vision technology [ 10 ], such as machine learning [ 11 , 12 ] and deep learning methods [ 13 , 14 , 15 ], a fully automatic process to measure the CA quickly and precisely can potentially overcome the shortcomings mentioned above. Digitalized X-ray images, processed through computerized learning, have previously been used to screen, diagnose, and classify severity of scoliosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digitalized X-ray images, processed through computerized learning, have previously been used to screen, diagnose, and classify severity of scoliosis [ 12 ]. Further development in deep learning has also led to an increase in different measuring and assessing CA [ 13 , 14 , 15 , 16 ]. Automatic detection of the spine anatomy in X-ray images to select the appropriate end vertebrae is an essential stage for CA measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation